STUDYING THE PARAMETERS OF MICROELEMENTS IN THE BLOOD OF CHILDREN WITH COMMUNITY-ACCOMPANIED PNEUMONIA - Shamsieva E.R. (Galaxy International Interdisciplinary Research Journal, 2022)
Community-acquired pneumonia (CAP) is an actual problem for pediatric practice. In recent years, there has been an increase in the incidence of CAP in children, and mortality from this disease remains relatively high. In real practice, especially in outpatient settings, early diagnosis and rational therapy of pneumonia in children are serious problems [1, 4, 8]. Meanwhile, over the past decades, a large amount of factual material has been accumulated on the significance of microelements for the human and animal organisms. Based on these data, copper, cobalt, zinc, selenium and other trace elements (14 in total) were identified as essential. Numerous clinical and experimental works are devoted to the study of the characteristics of metabolism and the significance of microelements in various pathological conditions [3,5,6]. The data of clinical studies on the microelement composition of the blood in children with acute pneumonia are not numerous and contradictory, meanwhile, in acute pneumonia, due to toxemia and impaired external respiration, compensatory-adaptive shifts occur in the homeostasis system, in particular, the content of microelements, as factors involved in oxygen transport, tissue respiration, detoxification and repair processes [7].